ChatGPT assists in identifying and recommending research study designs to support study protocol writing - Gary KK, Low; Osamudiamen Favour, Omosumwen; Sudarshan, Subedi; Sam Froze, Jiee; Wan-Hsuan, Lee; Sirjana, Devkota; Selvanaayagam, Shanmuganathan; Zelda, Doyle (Inderscience Enterprises Ltd., 2025)
This study aimed to validate ChatGPT by identifying the types of study designs in the published scientific literature and recommending the types of research study designs. ChatGPT Version 3.5 was asked to classify the published literature into different study designs. ChatGPT answers were then compared to the blinded independent reviewers' findings. The ChatGPT was then used to provide recommendations for study designs with the research titles from 333 unpublished study protocols. A total of 463 articles were used for validation. The Kappa coefficient was 84.45% agreement for the published literature. The agreement between ChatGPT and reviewers based on whole study protocol was 56.2%. ChatGPT may assist in classifying the types of study design with reasonably good accuracy if an abstract or full text is provided. ChatGPT may also be useful in recommending study designs to a novice researcher but with oversight from experts.